Identity, culture and development through participatory audiovisual: The Youth Path Project case from Costa Rica's UNESCO - Ángel V. Rabadán; Luis Bruzón; Sonia Montaño (Universidad Politécnica Salesiana, 2015)
In this article we present the use of audiovisuals media as a strategic element capable of integrating the concepts of culture and development, promoting intercultural dialogue and participation. The concept of cultural identity is present through coexistence and creativity of young people participating in the "Youth Path" program proposed by UNESCO and developed in Central America, in order to promote development strategies and inclusion. The ethnographic audiovisual, as a fundamental tool to generate knowledge processes and communication links and interaction.